Adsorption of Ni2+, Cu2+ and Co2+ ions on coal gangue-based porous ceramics - Zhou, Xiaopeng; Wang, Yongzhen; Lin, Renpeng; Zhou, Rui; Ma, Yue (Frontiers in Materials, 2025)
It is urgent to develop an adsorbent with low price and high removal rate of heavy metal cations for the treatment of wastewater. Herein, we report a novel coal gangue-based multiphase porous ceramic as an efficient and economic adsorbent for remove heavy metal cations. Due to the highly designed porous structure derived from the effect of pore-forming agents, the coal gangue-based multiphase porous ceramic adsorbent shows remarkable performance of the removal of Cu2+, Co2+, and Ni2+ from wastewater. Meanwhile, the microstructure and chemical composition of coal gangue-based porous ceramics have been characterized by X-Ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscope. Besides, the effects of the formula and particle size of silicon carbide on the structure of porous ceramics were also studied. Furthermore, the structure-function relationship between various reaction conditions and adsorption performance and the microstructure of adsorbent has been researched. In addition, the adsorption mechanism of complex porous ceramics on Cu2+, Co2+, and Ni2+ has been revealed by simulated calculation.